Possibilities of Studying Epidemics of Cholera in Upper Hungary (Contemporary Slovakia) in the 19th Century - Golian, Jan (Studia Historiae Oeconomicae, 2022)
We can conclude that epidemics in the 19th century reached historical populations in a new way. Sources from this period increasingly show a growing proportion of childhood as well as the arrival of a new strong epidemic of the adult population. It was cholera that decimated the adult population of the European continent, primarily, in several waves. These epidemics can be studied on the basis of different types of primary and secondary sources. In this article, I will present the possibilities of analyzing the primary statistical sources created by churches and the state. Reactions to the course of infectious diseases, applied measures or recommendations for treatment.